2022
DOI: 10.3390/ijerph19042203
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Therapy in Patients with Multiple Sclerosis—Review

Abstract: Multiple sclerosis (MS) is a chronic, autoimmune, demyelinating disease of the central nervous system (CNS). MS is an incurable disease. The goal of disease-modifying therapies (DMT) is to slow the progression of the disease, prevent relapses and increase the patient’s overall quality of life. According to the World Health Organisation definition, adherence means the extent to which a person’s medication-taking behaviour corresponds with the agreed upon treatment recommendations from a healthcare provider. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Regular distant and on-site monitoring visits were conducted. We reported in line with the STROBE statement [ 26 ].…”
Section: Methodssupporting
confidence: 78%
“…Regular distant and on-site monitoring visits were conducted. We reported in line with the STROBE statement [ 26 ].…”
Section: Methodssupporting
confidence: 78%
“…The SPMS subtype requires disability progression following the initial diagnosis of RRMS [ 3 ]. Several disease modifying treatments (DMTs) are currently in use in order to manage the ongoing disease activity in an attempt to control relapses and disability progression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, forgetfulness is the most common cause of poor adherence in our study and is also indicated in many studies. 5,13,23 To our knowledge, there are no studies in our country which address the five dimensions in the WHO model of medication adherence. In other regions, some studies identified several key factors associated with adherence, such as age, gender, disability, depression, cognition or treatment satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the variables "satisfaction with the neurologist", "presence of comorbidities" and "time since MS diagnosis (chronicity)" were initially considered for the multivariate analysis based on previous evidence. 8,13,23 Third, we applied the best subsets regression method with the goodness of fit (R 2 ) metric to identify the variables that best predict the adherence to MS treatment. One of the advantages of this method, compared to other common strategies such as stepwise regression, is the capacity to identify combinations of variables without eliminating any of them in the process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation